Analysis of Behavior-Based Safety Criteria with the Rate of Work Accidents at Power Plants Units 3, 7 and 8 East Java - Yunanto, Bekti; Indriastiningsih, Erna; Trisna Devi, Anita Oktaviana; Nugrahadi, Bekti (International Journal of Computer and Information System (IJCIS), 2025)
Occupational safety and health are important factors in the steam power generation industry which has a high risk of work accidents. The implementation of behavior-based safety at coal-fired power plants is useful for reducing the incidence of accidents through intervention on worker behavior. This study aims to analyze the relationship between behavior-based safety criteria and the rate of work accidents at PLTU Units 3, 7, and 8 in East Java. This study uses a quantitative approach with a cross-sectional design. Primary data was collected through questionnaires distributed to 178 workers, while secondary data was obtained from company safety reports. The results of the study show that there is a significant relationship between behavior-based safety and the rate of work accidents through the definition factors of safe/unsafe behavior, training, basic performance, reinforcement, feedback, goal setting, and reviews in PLTU Units 3, 7, and 8 workers in East Java. This variable contributes to increasing workers' awareness of safety and reducing the number of work accidents. Meanwhile,  the ownership variables) and observation did not have a significant relationship with work accidents, indicating the need for increased active worker participation and the effectiveness of follow-up from safety observations. The conclusion of this study is that behavior-based safety is an effective approach in reducing work accidents at coal-fired power plants, with factors such as safe/unsafe behavior, training, basic performance, reinforcement, feedback, goal setting, and review plays an important role in improving occupational safety. Companies need to strengthen training programs and monitoring worker behavior to achieve the zero accident target.